2009
DOI: 10.1007/s00109-009-0525-5
|View full text |Cite
|
Sign up to set email alerts
|

Sgk1 activates MDM2-dependent p53 degradation and affects cell proliferation, survival, and differentiation

Abstract: Serum and glucocorticoid regulated kinase 1 (Sgk1) is a serine-threonine kinase that is activated by serum, steroids, insulin, vasopressin, and interleukin 2 at the transcriptional and post-translational levels. Sgk1 is also important in transduction of growth factors and steroid-dependent survival signals and may have a role in the development of resistance to cancer chemotherapy. In the present paper, we demonstrate that Sgk1 activates MDM2-dependent p53 ubiquitylation. The results were obtained in RKO cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
88
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(98 citation statements)
references
References 50 publications
10
88
0
Order By: Relevance
“…It is reported that SGK can regulate cell viability through activation of MDM2-dependent p53 degradation (Amato et al 2009). Moreover, like AKT, SGK also exists in three isoforms (SGK1, SGK2, and SGK3) in human and mouse (Brunet et al 2001).…”
Section: Does Mtorc2 Regulate Cancer Cell Survival?mentioning
confidence: 99%
“…It is reported that SGK can regulate cell viability through activation of MDM2-dependent p53 degradation (Amato et al 2009). Moreover, like AKT, SGK also exists in three isoforms (SGK1, SGK2, and SGK3) in human and mouse (Brunet et al 2001).…”
Section: Does Mtorc2 Regulate Cancer Cell Survival?mentioning
confidence: 99%
“…SGK1 shares high sequence homology with AKT (∼50% through their catalytic domain) and a similar consensus phosphorylation site RXRXXS/ T with AKT (17), which negatively regulates p53 function through the activation of MDM2. A recent study reported that SGK1 negatively regulates p53 in several human cancer cell lines through the activation of MDM2 (18). This raises the possibility that the induction of SGK1 under chronic restraint may mediate the effect of glucocorticoids on p53.…”
Section: Sgk1 Mediates the Inhibitory Effect Of Glucocorticoids On P5mentioning
confidence: 99%
“…
Conflict of interest:The authors have declared that no conflict of interest exists.Nonstandard abbreviations used: SGK1, serum-and glucocorticoid-inducible kinase 1; RPL, recurrent pregnancy loss; ENaC, epithelial sodium channel; HESC, human endometrial stromal cells; ROS, reactive oxygen species; IVF, in vitro fertilization; dpc, days post coitus.
2Infertility and recurrent pregnancy loss (RPL) are prevalent but distinct causes of reproductive failure that often remain unexplained despite extensive investigations 1,2 .Analysis of mid-secretory endometrial samples revealed that SGK1, a kinase involved in epithelial ion transport and cell survival [3][4][5][6] , is upregulated in unexplained infertility, most prominently in the luminal epithelium, but downregulated in the endometrium of women suffering from RPL. To determine the functional significance of these observations, we first expressed a constitutively active SGK1 mutant in the luminal epithelium of the mouse uterus.
…”
mentioning
confidence: 99%
“…Analysis of mid-secretory endometrial samples revealed that SGK1, a kinase involved in epithelial ion transport and cell survival [3][4][5][6] , is upregulated in unexplained infertility, most prominently in the luminal epithelium, but downregulated in the endometrium of women suffering from RPL. To determine the functional significance of these observations, we first expressed a constitutively active SGK1 mutant in the luminal epithelium of the mouse uterus.…”
mentioning
confidence: 99%
See 1 more Smart Citation